Isolation and Molecular Cloning of Cellulase Gene from Bovine Rumen Bacteria - Rahadian Pratama; I Made Artika; Tetty Chaidamsari; Herti Sugiarti; Soekarno Mismana Putra (Current Biochemistry, 2014)
Cellulases are the enzymes that hydrolyze cellulosic biomass and are produced by the microorganisms that grow over cellulosic matters. The objective of this research was to isolate and clone cellulase gene from cellulose-degrading bacteria of bovine rumen. Cellulose-degrading bacteria was isolated from rumen fluid using a selective medium. Total RNA was isolated from selected colony having cellulose degrading activity and was used as a template for cDNA construction using reverse transcriptase polymerase chain reaction (RT-PCR) technique. The resulted cDNA was employed as a template for PCR amplification of cellulase gene using specific primers. The cellulase gene candidate obtained was cloned into the pGEM-T-Easy vector followed by determination of its nucleotide sequence. The sequence was then aligned with sequences of cellulase genes from GenBank. Results showed that a number of isolates of rumen bacteria exhibit cellulase activity and the CR-8 isolate was selected for further analysis. The successful isolation of total RNA from CR-8 was indicated by the presence of two intense bands of ribosomal RNA (23S and 16S). The reverse transcription process was successful and the amplification of cellulase gene using the specific primers F1 and R1 resulted in a DNA fragment of 1900 bp as a candidate of cellulase gene. The fragment was successfully cloned into the pGEM-T-Easy vector, and the resulted recombinant plasmid was successfully introduced into the E. coli cells. Nucleotide sequence analysis suggested that the cloned gene is cellulase gene and shares 99% homology with the endo-1,6-beta-glucanase of T. harzianum.